Oncofetal protein glypican‐3 is a biomarker and critical regulator of function for neuroendocrine cells in prostate cancer - Butler, William; Xu, Lingfan; Zhou, Yinglu; Cheng, Qing; Hauck, J. Spencer; He, Yiping; Marek, Robert; Hartman, Zachary; Cheng, Liang; Yang, Qing; Wang, Mu‐En; Chen, Ming; et al. (The Journal of pathology, 2023)
Neuroendocrine (NE) cells comprise ~1% of epithelial cells in benign prostate and prostatic adenocarcinoma (PCa). However, they become enriched in hormonally treated and castration‐resistant PCa (CRPC). In addition, close to 20% of hormonally treated tumors recur as small cell NE carcinoma (SCNC), composed entirely of NE cells, which may be the result of clonal expansion or lineage plasticity. Since NE cells do not express androgen receptors (ARs), they are resistant to hormonal therapy and contribute to therapy failure. Here, we describe the identification of glypican‐3 (GPC3) as an oncofetal cell surface protein specific to NE cells in prostate cancer. Functional studies revealed that GPC3 is critical to the viability of NE tumor cells and tumors displaying NE differentiation and that it regulates calcium homeostasis and signaling. Since our results demonstrate that GPC3 is specifically expressed by NE cells, patients with confirmed SCNC may qualify for GPC3‐targeted therapy which has been developed in the context of liver cancer and displays minimal toxicity due to its tumor‐specific expression. © 2023 The Pathological Society of Great Britain and Ireland.